2017
DOI: 10.1186/s12348-017-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bacterial Biofilm Formation on Soft Contact Lenses Using Natural Compounds

Abstract: PurposeIn eye care field, contact lenses (CL) have a great impact on improving vision, but their use can be limited by ocular infection. CL- associated infections can be reduced by good attention to CL storage case practice. CL-care solutions should be able to control microbial growth on CL.The aim of the study was to evaluate and compare the efficacy of CL-care solutions (found in Egyptian market) with some natural compounds in removal and inhibition of bacterial biofilm formed on soft CL.Clinical isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 41 publications
(41 reference statements)
2
27
1
3
Order By: Relevance
“…e biofilm formation rate found in this study is comparable with a study conducted in Chicago [44]. However, the comparatively lower biofilm formation rate was reported in Saudi Arabia [45]. P. aeruginosa (80%), K. pneumoniae (77.8%), CoNS (75.6%), S. aureus (72.4%), and E. coli (60%) were among the leading biofilm formers.…”
Section: Bacterial Isolatesupporting
confidence: 81%
“…e biofilm formation rate found in this study is comparable with a study conducted in Chicago [44]. However, the comparatively lower biofilm formation rate was reported in Saudi Arabia [45]. P. aeruginosa (80%), K. pneumoniae (77.8%), CoNS (75.6%), S. aureus (72.4%), and E. coli (60%) were among the leading biofilm formers.…”
Section: Bacterial Isolatesupporting
confidence: 81%
“…), Pseudomonas on contact lenses (El‐Ganiny et al . ) and Staphylococci in orthopaedic implants and breast implants (Arciola et al . ; Seng et al .…”
Section: Antimicrobial and Antifungal Properties Of Biosurfactantsmentioning
confidence: 99%
“…[75]. Calendulae flos extracts have well documented antimicrobial activity [19][20][21], especially polyphenols and essential oil, are useful in wound healing [76,77]. As shown in Table 4, it is noteworthy that the combination of the Calendulae flos lyophilized extract with chitosan did not exhibit a lower MBC value, in particular against pathogens responsible for wound infections.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effect on the wound healing process has been proven in numerous in vitro and in vivo studies, which were found to increase the proliferation and migration of human fibroblast and keratinocytes, stimulating angiogenesis and decrease collagen degradation after use of Calendulae flos extracts [14][15][16][17][18]. Furthermore, the Calendulae flos extract possesses some pharmacological features, which include antioxidant and anti-inflammatory action, as well as antibacterial, antifungal, and antiviral activity against various pathogens, e.g., Staphylococcus aureus, Escherichia coli, Bacillus cereus, and others [19][20][21].…”
Section: Introductionmentioning
confidence: 99%